Pengujian Alat Pemantauan Penggunaan Daya Listrik Menggunakan Web - Karliana Tiara Putri; Dodi Budiman Margana; Tjan Swi Hong (Politeknik Negeri Bandung, 2019)
Abstract - Problems of use by two or more people such as boarding children who are at one kWh of the still a problem, because the calculation of the electrical power used by the occupants of the calculation room is based on how much electronic equipment is in the room. In addition, it is often forgotten to turn off electronic equipment when it goes which causes waste of electricity. This final project aims to create a tool that can measure and monitor the use of electricity that is converted into the price of rupiah used by each room occupant through a web . The method used is measuring the amount of current and voltage on the load using current sensors and voltage sensors. Input data for computing on the microcontroller becomes rupiah then the sensor readings will be sent to the web server to monitor the use of electrical power that has been used. The results of testing the measurement of power measured by the system against the calculated power has an accuracy of 90% and monitoring data from the web as well as controls for disconnecting electricity through the web with an average delivery time of 5 seconds